Prevalence of Giardia Lamblia, Entamoeba Histolytica, Pin Worms and Cryptosporidium Parvum Parasites among People in Al - khoms City, Libya (Journal of Humanitarian and Applied Sciences, 2023)
Abstract:Intestinal Parasitic Infections are the most prevalent diseases in the world, predominantly in developing countries. Intestinal parasites are responsible for one of the major health problems like food contamination with socioeconomic effects in the world with a prevalence rate of 30-60%, in developing countries. This study aims determine the prevalence of four intestinal parasites that infect human in Al’khomes, namily Entamoeba histolytic, Giardia lamblia pin worms and cryptosporidium parvum. This study was conducted with 769 patients in the Al-Khoms teaching hospital, Al-khoms, Libya between March 2022 to August 2022. The prevalence rate was 401 (52.14%) for male and 368 (47.85%) for female. The prevalence of intestinal parasites was high in age group of 11-20 years compared to other age groups. The residence of patients lies in both urban (68.53%) and rural (31.46%) areas. In this study, four types of intestinal parasite were detected, namely: Giardia lamblia, Entamoeba histolytica, Pin worms and cryptosporidium parvum. The data on the prevalence of parasites with respect to gender, G. lamblia has more prevalence in male than the females. But E.histolytica and Pin worms presents more in female cases than the male cases. From the participate 769 people, 93.76% of people were healthy and not detected any kind of parasitesites in their intestinal area. Further, with respect to age, children and teenagers had surplus parasites compared to old age groups. These parasites could be prevented by possible grouping of better ecological design and hygiene. Conclusively, the examination of personal hygiene as well as routine medical examination and treatment is strongly recommended in the low socio-economic areas.
Keywords: Intestinal parasites; Intestinal parasitic infection; Giardia Lamblia; Entamoeba histolytica; Libya